Analysis of The Influence of Website Application Quality, Service Quality and Trust on Consumer Decisions to Transact on Gojek Applications in the Pier Industrial Area of Pasuruan District - Hasnawaty Ismail (Eduvest - Journal of Universal Studies, 2025)
The ride-hailing industry in Indonesia, with GOJEK as a prominent player, has experienced rapid growth, significantly impacting urban mobility and creating vast opportunities in the online business sector. GOJEK, offering services like ojek transportation, food delivery, and digital payments, has been downloaded over 190 million times in Indonesia. Despite its popularity, consumers continue to voice complaints regarding app functionality, service quality, and trust. This study aims to explore how website application quality, service quality, and trust influence consumer decisions to use GOJEK services, particularly in the PIER Industrial Estate of Pasuruan Regency, an area with a large working population and high usage of online transportation. Using a quantitative approach, the research surveys GOJEK users who work or intern in the area, analyzing factors like app quality, service reliability, and trust in the driver and app. The study's findings aim to identify the key determinants that shape consumers' decisions to use GOJEK, offering insights to optimize company strategy and user experience. This research is expected to benefit business practitioners, academics, and policymakers by providing valuable information to improve service quality and enhance consumer loyalty in industrial zones and beyond. Additionally, the study is intended to contribute to the advancement of management theory and offer practical recommendations for ride-hailing companies to refine their services, marketing strategies, and build a foundation for future research in the field.